(untitled) (Actual Problems of Psychology in Educational Institutions, 2022)
The article is devoted to the study of the role of the family in the formation of gender attitudes of the role behavior of the adolescents. The importance of the family as an agent of the socialization of youth in an unstable society has been determined. The manifestations of subjective representations of senior pupils about the distribution of functional roles between family members are investigated. The domination in the world outlook of girls of more egalitarian gender attitudes in comparison with young men is ascertained. The conclusion is made about the need to harmonize the educational principles of the family and the school in the formation of a culture of gender behavior.